Determinants of FDI Inflows in Agriculture Sector Using Pooled Ordinary Least Square (OLS), Pooled Generalized Least Square (GLS), Augmented Dickey-Fuller (ADF) and Philips-perron Unit Root Test - Maizura Abd Rashid, Intan; Azizah Abd Rahman, Nur; Ahmad Fauzi Wan Husain, Wan; Fitri Mansor, Mohd; Hanie Abu Samah, Irza; Harith Amlus, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
This paper presents the importance of poverty reduction, technology advancement, infrastructure, and inflation rate on foreign direct investment inflows in the agriculture sector. The countries selected in this study, which are the Czech Republic, Hungary, Latvia, Poland, and Slovenia, which are categorized as OECD countries, need to address important challenges through determined implementation of structural reforms. This study applies the empirical analysis and focuses on some variables, which are FDI in agriculture, poverty, inflation, technology advancement, and infrastructure. Data from 2005 to 2014 were collected to determine the relationship among the variables. The models that were being used are Ordinary Least Square (OLS) and Generalized Least Square (GLS), Unit Root Test based on Augmented Dickey-Fuller (ADF) test, and Unit Root Test based on Philips-Perron Test. Tests were performed to examine the causal relationship between poverty and FDI in agriculture, inflation and FDI in agriculture, technology advancement and FDI in agriculture, and infrastructure and FDI in agriculture.